THE EFFECT OF INCLUSIVE LEADERSHIP ON WORKPLACE BULLYING WITH SELF-ESTEEM AS MEDIATION - Nurliza; Jeni Wardi; Adi Rahmat (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This research aims to analyze the effect of inclusive leadership on workplace bullying with self-esteem as a mediating variable. The study was conducted at the Department of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) of Siak Regency, involving 51 respondents. The research method used is a quantitative approach with saturated sampling technique (census). Data were collected using questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with SmartPLS 3.2.9 software. The results show that: (1) Inclusive leadership has a positive and significant effect on self-esteem, (2) Inclusive leadership has a positive and significant effect on workplace bullying, (3) Self-esteem has a positive and significant effect on workplace bullying, and (4) Self-esteem mediates the effect of inclusive leadership on workplace bullying. These findings indicate the important role of inclusive leadership and self-esteem in reducing workplace bullying behavior.